Cosmological Reproducers of Discourses of Power: the Obelisks of the New Kingdom: Los obeliscos del Reino Nuevo - Neira Cordero, Elisa (Centro de Estudios Históricos. UA CONICET, 2023)
The aim of this paper is to understand the meaning of the practice of construction and placement of obelisks in ancient Egypt from the analysis of the characteristics of these monuments and the different contexts in which they intervened. We have considered a diachronic perspective, in order to identify whether this practice generated worldview changes in the New Kingdom, specifically under the Eighteenth Dynasty. Heliopolis was the main site of obelisks since the Old Kingdom (ca. 2543-2120 BC). During the Middle Kingdom (ca. 1908-1760 BC) Senusret I maintained this practice there, although he made changes, and from the New Kingdom (ca. 1539-1077 BC) the obelisks were placed next to the pylons from the temples. In this context, the obelisk was considered a building related to the cult of Ra that allows the reproduction of ancient Egyptian cosmology. We consider this type of monument as part of a political discourse carried out by the pharaohs, especially during the Eighteenth Dynasty (ca. 1539-1292 BC), when the first pair of obelisks was placed in Thebes, the place of origin of the Ahmoside dynasty that reunified the state.